Conservation implications of using an imitation carnivore to assess rarely used refuges as critical habitat features in an alpine ungulate - Sarmento, Wesley; Berger, Joel (PeerJ, 2020)
Understanding relationships between animals and their habitat is a central goal in ecology with important implications for conservation. Misidentified habitat requirements can have serious repercussions because land protection or reintroductions might occur in less than optimal habitat. Studies of resource selection have greatly facilitated an understanding of ecological relationships but can be improved when vital yet infrequently utilized habitat features are more fully described. A critical element for many prey species is escape terrain or some other form of refuge to avoid predation. Mountain goats (Oreamnos americanus) are well known for their use of cliffs to avoid predation, but a survey of the literature revealed at least twelve different approximations of goat escape terrain, ranging from > 25° to > 50° slopes. Here, we seek to (1) enhance estimates of mountain goat escape terrain and antipredator behavior, and (2) highlight the limitations of the assumption that the time an animal spends in an area is proportional to importance. To improve estimates of goat escape terrain, we conducted field work across two years (2014–15) in Glacier National Park, Montana USA and manipulated apparent predation risk by exposing mountain goats to a threatening simulated grizzly bear (Ursus arctos) treatment and a non-threatening ungulate (control) treatment. Mountain goats moved in response to the simulated bear but not in response to the simulated ungulate, with shorter latencies to move for subjects in larger groups and at shorter distances to the simulated threat. Through a used-unused resource selection function we tested 22 landscape variables to describe the use of escape terrain. Proximity to slopes greater than 60° best explained the locations to which mountain goats fled after exposure to the simulated bear, and the average slope of these escape locations was 56.5° (±14.1 S.D.). Our results suggest that mountain goat escape terrain be considered at slopes of 60° as a minimum because our simulated threat did not include pursuit of goats and, thus, slopes of 60° are likely underestimates of actual escape terrain. Additionally, because direct interactions between carnivores and goats seldom occur, serious escape terrain is infrequently used. Past estimates of escape may have miscalculated the slopes which goats select for in response to predation risk. Based on experimental approaches in the wild, we suggest that anti-predator behavior should be included in studies of resource selection when the goal is to consider habitat as a predictor for conservation success. Finally, we discuss evidence suggesting a past mountain goat introduction failed due to lack of adequate escape terrain and subsequent recolonization of a predator.
Keywords: Anti-predator; Predation risk; Mountain goat; Predator-prey; Resource selection; Oreamnos americanus; Fear; Predation refugia; Security habitat optimization; Harvest